2009
DOI: 10.1111/j.1399-0012.2008.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rituximab therapy for treatment of acute humoral rejection

Abstract: Addition of rituximab improved the outcomes of PP treatment of antibody mediated rejection episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 38 publications
0
78
1
1
Order By: Relevance
“…The safety profile of RTX in this population remains unclear, however, with conflicting data on its association with infectious complications [3,[7][8][9][10][11][12][13][14]. This study of 55 kidney transplant patients treated with RTX for its common peri-and posttransplant indications favors an association an increased risk of infections with RTX.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The safety profile of RTX in this population remains unclear, however, with conflicting data on its association with infectious complications [3,[7][8][9][10][11][12][13][14]. This study of 55 kidney transplant patients treated with RTX for its common peri-and posttransplant indications favors an association an increased risk of infections with RTX.…”
Section: Discussionmentioning
confidence: 91%
“…T-lymphocyte depleting preparations in particular have been associated with an increased risk, as opposed to nonlymphocyte depleting agents which demonstrated similar infectious risks when compared to placebo [5,6]. RTX has generally been considered to have an acceptable safety profile in hematological and autoimmune disorders; however, whether it can be used without an increased risk of infectious complications remains controversial in the immunosuppressed population [3,[7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data also report an anti-rejection activity of Rituximab (Kaposztas Z et al, 2009;Mulley WR et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…13,14 Other strategies for managing ABMR include the use of rituximab, which targets pre-B cells and B cells, and bortezomib, which is a proteasome inhibitor. 15,16 Uncontrolled randomised studies have shown benefit in both rituximab and bortezomib. 11,17 These agents are usually used in conjunction with IVIG and/or PLEX.…”
Section: Discussionmentioning
confidence: 99%